PERIODESASI PERKEMBANGAN PEMIKIRAN DALAM HUKUM ISLAM (Suatu Telaah Historis-Kultural) - Djamila Usup (IAIN Manado, 2008)
The article discusses the development of thought in the field of Islamic jurisprudence emphasizing on its historis-cultural aspects.The writer mainly argues that the Islamic law that rooted from the Holly Qur’an and Hadits has been ackowledged to be always compatible untill the end of the world.In practice and implementation,however,adjusments are often made to suit the current situation whilst maintaining the universal principle from which they are originated.The thought/contemplation of Islamic law is establised to investigate how Islamic law could cope with the sociocultural feature of the surounding community.